2020
DOI: 10.1007/s10072-020-04695-w
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and its impact on neurological manifestations and mental health: the present scenario

Abstract: Though the COVID-19 pandemic primarily affects pulmonary and cardiorenal functions, many healthcare and its allied groups reported neurological involvement of SARS-CoV-2 in combination with either pre-existing metabolic abnormalities, medical conditions, infections or even chronic to acute inflammatory episodes of the nervous system. The present review provides a fair outlook of the published literature and also the case reports with an emphasis on plausible mechanisms involved in neurological complications of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
8

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 59 publications
0
18
0
8
Order By: Relevance
“…The specific neurological symptoms in COVID-19 patients normally include acute cerebrovascular disease, ataxia, seizure, cranial nerve involvement, and neuroinflammationassociated neurological disorders (Asadi-Pooya and Simani, 2020; Beyrouti et al, 2020;Kempuraj et al, 2020). In addition to direct CNS invasion, microthrombosis, severe hypoxemia, and neurological side effects of antiviral medications, the mechanism of gut microbial dysbiosis has been proposed to explain the neurological damage produced by COVID-19 (Sultana and Ananthapur, 2020;Whittaker et al, 2020). Alteration of the composition of the gut microbiota during intestinal SARS-CoV-2 infection could be involved in the pathogenesis of neuropsychiatric symptoms via the gut-brain axis, including the immunological, hormonal, and neuronal pathways.…”
Section: Involvement Of Gut Microbiota In Covid-19mentioning
confidence: 99%
“…The specific neurological symptoms in COVID-19 patients normally include acute cerebrovascular disease, ataxia, seizure, cranial nerve involvement, and neuroinflammationassociated neurological disorders (Asadi-Pooya and Simani, 2020; Beyrouti et al, 2020;Kempuraj et al, 2020). In addition to direct CNS invasion, microthrombosis, severe hypoxemia, and neurological side effects of antiviral medications, the mechanism of gut microbial dysbiosis has been proposed to explain the neurological damage produced by COVID-19 (Sultana and Ananthapur, 2020;Whittaker et al, 2020). Alteration of the composition of the gut microbiota during intestinal SARS-CoV-2 infection could be involved in the pathogenesis of neuropsychiatric symptoms via the gut-brain axis, including the immunological, hormonal, and neuronal pathways.…”
Section: Involvement Of Gut Microbiota In Covid-19mentioning
confidence: 99%
“…As several studies demonstrated that SARS-CoV-2 infection can affect the central nervous system [3][4][5], we could consider it as a likely causal factor in DG. Presence of vascular risk factors in our patient is consistent with recent evidence suggesting that acute cerebrovascular events related to COVID-19 are more frequent in patients with severe respiratory distress and common cardiovascular risk factors [3].…”
Section: Main Textmentioning
confidence: 99%
“…Ageusia and anosmia are further relevant signs of nervous system involvement in SARS-CoV-2 infection [4].…”
Section: Main Textmentioning
confidence: 99%
“…More than onethird of COVID-19 patients present neuropsychiatric symptoms during the course of the disease. Even in some patients, neurologic symptoms may be the initial or only presentations of the COVID-19 [2]. An association between major depressive disorder (MDD), alexithymia, and negative complications such as suicidal behavior in COVID-19 patients has been described.…”
Section: Introductionmentioning
confidence: 99%